Hubungan Antara Pengetahuan dan Sikap Terhadap Tindakan Pencegahan Penyakit Chikungunya pada Keluarga di Desa Kepenuhan Timur , Kec. Kepenuhan, Kab.Rokan Hulu, Propinsi Riau. - Tuti Restuastuti; Yuliawati Yuliawati; Suri Dwi Lesmana (Fakultas Kedokteran Universitas Riau, 2011)
Chikungunya is a viral illness that is caused by Chikungunya virus and transmitted by Aedes sp. The purpose of thisresearch was to determine the relationship between knowledge and attitude with practice of chikungunya diseaseprevention to families in Kepenuhan Timur village Kepenuhan Subdistrict Rokan Hulu regency. The method of thisresearch was analytic crossectional study. The sample size were 230 families. The amount of subject were determindusing simple random sampling. The data were collected by using questionaires. The results of this research showedthat 64,3% of respondent had lack of knowledge, 99,1% of respondent had positive attitudes and 84,8% of respondentshad negative behavior in chikungunya disease prevention. There was no significant relationship between knowledgeand attitudes with practice of chikungunya disease prevention in Kepenuhan Timur village with p value > 0,05.